Livestock farmers’ involvement in goat production in Aniocha north local government area of Delta State, Nigeria - Emaziye, P. O.; Ikpoza, E. A.; Ebewore, S. O. (International Journal of Agricultural Technology, 2021)
The study assessed the level of livestock farmers’ involvement in goat production in Aniocha North of Delta State, Nigeria. The obtained results showed that most of the farmers were not involved in goat production. The reasons adduced for non-involvement of farmers in goat production was the destructive nature of goats (mean = 4.87), stealing (mean = 4.85), diseases (mean = 4.84), poor management (mean = 4.78), shortage of food (mean = 4.70) and cost of purchase of initial stock (mean = 4.64). The t-test indicated that there was a significant difference between total revenue and cost of rearing at p< 0.05. The result of the logit regression showed that only two of the variables, flock size and household size, were significant in determining the respondents’ involvement in goat production. It was recommended among others that farmers in the study area should be enlightened on the benefits of keeping goats